Analysis of the internal control system in gas stations - Firman, Muhammad Salsabil Kautsar; Khudri, Tubagus Muhammad Yusuf (International Journal of Financial, Accounting, and Management, 2025)
Purpose: This Study aims to analyze the internal control system in the expenditure cycle and revenue cycle at PT HM Batarai's gas stations and provide recommendations to improve the effectiveness of its internal control system. Methodology/approach: The method used is a descriptive qualitative with a case study approach at the PT HM Batarai’s gas station. The primary and secondary data were validated using triangulation by observing gas station activities, conducting interviews with company management, and analyzing company documents. Results/findings: The results show that the internal control system of PT HM Batarai is ineffective due to the absence of supporting documents such as company regulations and integrity pacts, the lack of a risk management function, the absence of written processes and policies regarding company activities, and the lack of evaluation conducted on the internal control system. Limitations: This study is limited to evaluating the internal control system in the revenue and expenditure cycles implemented by PT HM Batarai using the COSO 2013 conceptual framework. Contribution: This study can serve as an evaluation resource for the management of PT HM Batarai, enabling them to enhance the effectiveness of the company's internal control system. Novelty: This study used a case study at a gas station, a critical business unit in the energy sector that heavily relies on cash, but this has yet to be discussed much. Keywords: Internal Control, Gas Station, Revenue Cycle, Expenditure Cycle